«WITH LANGUAGES, YOU ARE AT HOME ANYWHERE»: ABOUT IMPORTANCE OF MASTERING UKRAINIAN FOR FOREIGN STUDENTS - Velykozhon, Viktoria (Studies in Comparative Education, 2017)
The article highlights the importance of studying the Ukrainian language as foreign language for foreign students. Teaching experience shows that there are stu-dents who are consciously interested in learning Ukrainian language, not Russian. Consequently, a large number of students from different countries in Ukrainian higher educational institutions who have a great desire for learning the language of the country in which they are living, studying and planning to work caused the actuality of this article. The article also emphasizes the importance of the broader inclusion of the Ukrainian language subject for foreigners in the curricula of higher educational institutions of Ukraine, which will contribute to the modernization and renovation of the national educational sphere and better and faster formation of cross-cultural competence and socio-cultural adaptation of foreign students who, besides the language barrier, face many psychological problems in everyday life. The teacher's position is central in the educational process. The successful dialogue with the student depends on his professionalism, competence, humanity, tolerance and respect. Therefore, the article also examines the main didactic principles and analy-ses the main components that contribute to the learning of the Ukrainian language as a foreign language and which are necessary for each language teacher. The article distinguishes the methods, techniques, principles, the skilful use of which makes the process of learning the language more informative, interesting, meaningful, comprehensible, productive and stress-free. And as a consequence – the fluency in the Ukrainian language mastering is better for adaptation to new living conditions, sociocultural models of behavior, understanding the Ukrainian mentality.